On the Differential Uniformity and Nonlinearity of a Class of Permutation Quadrinomials Over $\mathbb{F}_{2^{2m}}$ (Communications in Mathematical Research, 2022)
Permutation polynomials with low differential uniformity and highnonlinearity are preferred in cryptographic systems. In 2018, Tu, Zeng andHelleseth constructed a new class of permutation quadrinomials over the finitefield $\mathbb{F}_{2^{2m}}$ for an odd integer $m$. In this paper, we aim to investigate the differential uniformity and nonlinearity of this class of permutation polynomials soas to find 4-uniform permutation polynomials with high nonlinearity.
Keywords: Differential uniformity; finite field; nonlinearity; permutation polynomial.